The Emergence Of Wireless Broadband Services In Malaysia : A Case Study On Worlddone (M) Sdn. Bhd. - Chin, Celine Lai Yin (2003)
The case study is on the emergence of wireless broadband services in Malaysia with WorldONE playing the lead role into bringing this new broadband technology to be "the way to communicate in the next generation communication".